Experimental and Numerical Investigations to Assess the Performance of a Buried Pipe Subjected to Traffic Load / Non-Treated and Cement-Treated Trench - Mosadegh, Ahdyeh (Curtin University, 2018)
In this research, the performance of buried flexible pipe subjected to traffic load was investigated. First, a numerical parametric study was performed to study the influence of eight factors on pipe-soil behaviour under surface load using ABAQUS. Then, the impact of surface pressure, burial depth, number of cycles and cement stabilization on model response was investigated using laboratory experiments and numerical simulations. Equations were developed using Linear Regression Model and Artificial Neural Network using MATLAB.